Efficacy of Different Root Canal Irrigants on Smear Layer Removal after Post Space Preparation: A Scanning Electron Microscopy Evaluation - Mirseifinejad, Rahele; Tabrizizadeh, Mehdi; Davari, Abdolrahim; Mehravar, Fateme (Iranian Endodontic Journal, 2017)
Introduction: Effective durable adhesion between post material and dentine using resin cements is essential for longevity of restoration. The aim of this in vitro study was to compare the effect of different irrigants on smear layer removal after post space preparation. Methods and Materials: A total of 75 extracted anterior human teeth were selected. The canals were instrumented by rotary system and then were filled. After preparing the post space, teeth were divided into 5 groups according to irrigants: 17% EDTA; 17% EDTA+2% CHX; 5.25% NaOCl; 17% EDTA+5.25% NaOCl; and saline. The canals were irrigated with 5 cc of each irrigants for 1 min. Specimens were examined with scanning electron microscopy (SEM). Hulsmann’s score was used for marking of smear layer removal at coronal, middle and apical thirds of post space. The data were analyzed using the Kruskal-Wallis and Mann-Whitney U tests. Results: The results revealed that subsequent use of 17% EDTA+5.25% NaOCl was more effective than the other groups in smear layer removal. No statistical difference was found among different levels of root canal within each group. Conclusion: It can be concluded that 17% EDTA+5.25% NaOCl could be an effective irrigant for smear layer removal after post space preparation. Keywords: Post Space; Root Canal Irrigant; Scanning Electron Microscopy; Smear Layer